2020
DOI: 10.1084/jem.20200275
|View full text |Cite
|
Sign up to set email alerts
|

High microbiota reactivity of adult human intestinal IgA requires somatic mutations

Abstract: The gut is home to the body’s largest population of plasma cells. In healthy individuals, IgA is the dominating isotype, whereas patients with inflammatory bowel disease also produce high concentrations of IgG. In the gut lumen, secretory IgA binds pathogens and toxins but also the microbiota. However, the antigen specificity of IgA and IgG for the microbiota and underlying mechanisms of antibody binding to bacteria are largely unknown. Here we show that microbiota binding is a defining property of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
79
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 35 publications
2
79
1
Order By: Relevance
“…demonstrated that mutations of the antigen-binding Fab domain of gut antibodies from control donors or patients with Crohn's disease (CD) confer crossspecies reactivity to the commensal microbiota (Kabbert et al, 2020). Intestinal antibodies include immunoglobulin A (IgA) dimers and IgM pentamers, which accumulate in the gut lumen as a result of a close cooperation between plasma cells and epithelial cells (Chen et al, 2020b).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…demonstrated that mutations of the antigen-binding Fab domain of gut antibodies from control donors or patients with Crohn's disease (CD) confer crossspecies reactivity to the commensal microbiota (Kabbert et al, 2020). Intestinal antibodies include immunoglobulin A (IgA) dimers and IgM pentamers, which accumulate in the gut lumen as a result of a close cooperation between plasma cells and epithelial cells (Chen et al, 2020b).…”
mentioning
confidence: 99%
“…To address this question, a wellestablished methodology (Tiller et al, 2008) was used to generate recombinant monoclonal antibodies from the terminal ileum of control or CD donors (Kabbert et al, 2020). These antibodies were obtained by PCR-amplifying Ig variable heavy chain (VH) and variable light chain (VL) gene products from single-cell sorted gut IgA + or IgG + plasma cells (see panel A in the figure).…”
mentioning
confidence: 99%
See 3 more Smart Citations